Kontribusi Mahasiswa dan Prodi Manajemen Pendidikan Islam (MPI) Dalam Kegiatan Program Latihan Profesi (PLP) - siswanto siswanto; Syaiful Bahri; Dian Bastian (STAI Ma'had Aly Al-Hikam Malang, 2022)
At the time of professional training program (PLP) activities, the active role of students is very much needed, therefore, between the theories obtained in lectures, can they be applied to internships at PLP locations. This study aims to describe how the contribution of students and study programs to PLP activities and how the impact of PLP on students, study programs and institutions where internships are. Then this research is a qualitative research that uses a qualitative descriptive approach. Data obtained through interviews, observation and documentation. Furthermore, the data obtained were analyzed by the theory of Miles and Hubermen. The research findings are: first: Student contributions, namely student participation in PLP activities at the Ministry of Religion, are very large based on their respective places or internship spaces, for example participating in making correspondence, data on Hajj and Umrah pilgrims, inputting dapodik data etc., then contributions The study program in PLP activities is to provide administration related to these activities, from briefing, finding locations to preparing administration for pick-up. The second impact of PLP for students is increasing knowledge and knowledge related to administrative processes in the office of the ministry of religion, training discipline and adding friends and family. As for the study programs, they can cooperate or collaborate well and make input materials for improving the study program curriculum and the quality of MPI study study students. Furthermore, for the agency where the internship is, the impact can help complete the tasks in the office well and can help in matters related to their work.